Compliance Of Diabetes Mellitus Patients In Controlling Blood Sugar Levels In Dahana Village, Sub-District Bawolato 2021 - Jagentar Perlindungan Pane; Ice Septriani Saragih; Nurtalenta Lafau (Sean Institute, 2022)
Diabetes mellitus is a metabolic disorder that occurs due to hyperglycemia that occurs due to abnormalities in insulin secretion, insulin work, or excess. Diabetes mellitus is a collection of symptoms that arise in a person caused by an increase in blood glucose levels. This research aims to see an overview of the level of Diabetes Mellitus patients in controlling blood sugar levels in Dahana village, Bawlato sub-district in 2021. The sampling technique was total sampling. With a total of 30 respondents. The measuring tool is a questionnaire. The results showed that the most respondents who suffered from diabetes mellitus aged 40-45 years were 14 people (46.7%). the most female respondents were 16 people (53.3%). most of the respondents were disobedient as many as 18 people (60.0%). From this research,